Ethics in Decision-Making: A Bibliometric Study of Emerging Trends in Financial Management - Assyfha Nisrina Rahma; Nur Syamsiyah Fauziyah; Restu Amalia; Rifatul Hasanah; Muhammad Aditya Saputra; Lusiana Desy Ariswati; Muhammad Ramadhani Kesuma (Indo Publishing, 2026)
Ethics in decision-making has become a fundamental aspect of financial management, as decision-makers frequently navigate dilemmas between achieving financial objectives and upholding moral values such as transparency, fairness, and social responsibility. Originating from business ethics scholarship, this concept emphasizes that financial decisions should not rely solely on economic rationality but must also incorporate ethical principles to prevent conflicts of interest and misuse of authority. n practice, ethics influences fund allocation, financial reporting, risk management, and corporate governance. Violations of ethical principles may precipitate corporate scandals and significantly erode public trust in organizations. Over time, discourse on ethics in decision-making has evolved through the integration of behavioral perspectives, corporate governance frameworks, and emerging technologies such as artificial intelligence (AI) for detecting potential ethical biases. However, systematic studies that comprehensively map the intellectual development of this field remain relatively limited. Therefore, this study applies a bibliometric analysis approach to identify publication trends, research collaboration patterns, and emerging thematic clusters in ethics in decision-making scholarship, drawing on 400 peer-reviewed articles sourced from the Scopus database covering the 2000s to the present.